Glacial‐Interglacial Climate Cycles of Atmospheric Hg Deposition: Insights From Hg Isotopes in Loess‐Paleosol Sequences on the Chinese Loess Plateau - Wen Xue; Zhidong Xu; Xing Cheng; Longfei Gou; Maoyong He; Zhangdong Jin; Miling Li; Linchuan Fang; Runsheng Yin (Geophysical Research Letters)
Abstract As a highly volatile heavy metal, Hg is transported over long distances in the atmosphere and enters global ecosystems via Hg(II) wet deposition and Hg(0) dry deposition. The Chinese Loess Plateau develops loess‐paleosol sequences (eolian deposits) reflecting glacial‐interglacial cycles. Here, we investigate the Hg concentration and isotopic composition of loess‐paleosol sequences covering three glacial‐interglacial cycles (spanning 350–80 ka). Paleosol layers display higher THg, Δ199Hg, and Δ200Hg values than loess layers, meaning enhanced Hg(II) wet deposition during interglacials. Based on a Δ200Hg‐based mixing model, Hg(II) wet and Hg(0) dry depositions account for 42% and 58% of Hg input into the Chinese Loess Plateau during interglacials but 21% and 79% during glacials, respectively. This work highlights a strong climatic control on atmospheric Hg deposition at glacial‐interglacial time scales, and suggests that atmospheric Hg deposition will likely increase in middle latitudes without considering perturbations of anthropogenic emissions.